2021
DOI: 10.1186/s12911-021-01413-0
|View full text |Cite
|
Sign up to set email alerts
|

Quality and readability of web-based Arabic health information on periodontal disease

Abstract: Background Currently, the Internet seems to be a helpful tool for obtaining information about everything that we think about, including diseases, their prevention and treatment approaches. However, doubts exist regarding the quality and readability of such information. This study sought to assess the quality and readability of web-based Arabic information on periodontal disease. Methods In this infodemiological study, the Google, Yahoo!, and Bing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
33
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 27 publications
9
33
2
Order By: Relevance
“…We used a graphic representation to show the key elements of our findings ( Figure 1 ). Overall, the participants expressed a preference for using the internet as a source of health information in comparison with other health information sources, which was consistent with previous studies with both English-and Arabic-speaking internet users [ 3 , 12 ]. Participants provided convenience, anonymity, and accessibility of OHI as reasons for using OHI.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We used a graphic representation to show the key elements of our findings ( Figure 1 ). Overall, the participants expressed a preference for using the internet as a source of health information in comparison with other health information sources, which was consistent with previous studies with both English-and Arabic-speaking internet users [ 3 , 12 ]. Participants provided convenience, anonymity, and accessibility of OHI as reasons for using OHI.…”
Section: Discussionsupporting
confidence: 88%
“…Laugesen et al [ 29 ] explained that physicians have a greater impact on patient’s health outcomes and compliance than internet health information. Concerns expressed by physicians in this study about the quality of health information on the internet and access to reliable websites followed similar studies [ 12 , 30 ]. Broom et al [ 24 ] recommended that to promote the impact of OHI on health, physicians should consider it as a complementary tool, rather than reflecting a breakdown in their authority or status.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The Google Trends tool and selected search engines were used to retrieve information on breast cancer using related Arabic terms [ 30 ]. Google trends tool analyzes data from the Google search engine.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, studies have reported lower readability and quality of information on Arabic websites [ 21 ]. This may impose a language barrier for disadvantaged individuals who are older or those with lower educational levels.…”
Section: Discussionmentioning
confidence: 99%